2023
DOI: 10.31083/j.fbl2808160
|View full text |Cite
|
Sign up to set email alerts
|

Rab2 and Rab6 are Implicated in Acrosome Formation during Spermatogenesis in Eriocheir sinensis: Based on Sperm Proteome

Abstract: Background: Rab proteins are GTP-dependent small proteins that function as regulators of intracellular vesicle transport, fusion, and localization. However, few studies have investigated their function in Decapoda reproduction. The Eriocheir sinensis sperm has no tail and the nuclei are uncondensed. With the acrosome forming the majority of the sperm mass, it provides an ideal model for studying acrosome formation. Methods: We firstly analyzed the sperm proteome using LC-MS/MS. To study the functions of Rab2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Consistent with GARIN1A and GARIN1B, we found other members of the GARIN family, GARIN2, GARIN3, GARIN4, GARIN5A, and GARIN5B, could interact with RAB2A/B that was suggested to function in acrosome biogenesis in several species [ 13 , 31 , 32 ]. Further, RT-PCR analyses revealed that Garin2-5b were expressed predominantly in testes.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with GARIN1A and GARIN1B, we found other members of the GARIN family, GARIN2, GARIN3, GARIN4, GARIN5A, and GARIN5B, could interact with RAB2A/B that was suggested to function in acrosome biogenesis in several species [ 13 , 31 , 32 ]. Further, RT-PCR analyses revealed that Garin2-5b were expressed predominantly in testes.…”
Section: Discussionsupporting
confidence: 64%